Charge-ordering induces magnetic axes rotation in organic materials (TMTTF)2X (with X = SbF6, AsF6, and PF6) - Dutoit, C.-E.; Bertaina, S.; Orio, M.; Dressel, M.; Stepanov, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
We have performed a comprehensive EPR investigation of the quasi-one-dimensional organic systems (TMTTF)2X with centrosymmetrical anions X (X = SbF6, AsF6, and PF6). We observe a strong rotation of g-factor principal axes when the temperature decreases below charge-ordering temperature TCO. The possible origin of this rotation is analyzed on the basis of quantum chemical calculations performed using density functional theory method. A good agreement between theory and experiment is found.